Improving Psychological Well-being of Adolescents through Character Strength Training - Tazkiya Tsaqofi, Fida; Yuwono, Susatyo (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to determine the effectiveness of character strength training in improving youths’ psychological well-being. Methodology: This study applied a quasi-experimental method with a pretest-posttest control group design involving 40 participants of SMPN 1 Ambarawa as experimental and control groups. The data collection method used a psychological well-being scale adapted from the Ryff scales of psychological well-being. The participants were adolescents aged 12-15 years and had low and moderate level of psychological well-being selected through screening. The hypothesis is character strength training can improve psychological well-being of adolescent. Result: Based on Independent T-Test, the result shows that the hypothesis is approved. The experimental group reached a mean value of 29.25 and the control group reached a value of 11.90 with a significance (2-tailed) value of 0,000 <0.005. Then, the value of the t-count was 6.009> while the value of the t-table was 2,024. In the experimental group, the Paired Sample T-Test showed a mean value of 146.60 and 175.70 for the post-test with a significance (2-tailed) = 0,000 <0.005 and the t-test result reached 12,666> with the t-table value of 2,093. Character strength training is effective to increase psychological well-being of adolescent.